Passing Probation: Earnings Management by Interim CEOs and Its Effect on Their Promotion Prospects - Chen, Guoli; Luo, Shuqing; Tang, Yi; Tong, Jamie Y. (Academy of Management Journal, 2015)
Drawing on chief executive officer (CEO) succession research and the impression management literature, we examine earnings management by interim CEOs, its impact on interim CEOs’ promotion prospects, and the moderating effect of governance mechanisms on the relationship between the two. Based on a sample of 145 interim CEO succession events in U.S. public firms from 2004 to 2008, we find that (a) an interim CEO is more likely than a noninterim CEO to engage in earnings management to improve firm earnings performance (“income-increasing earnings management”), (b) the greater the income-increasing earnings management, the more likely it is that the interim CEO will be promoted to the permanent position, and (c) the relationship between earnings management and the likelihood of interim CEO promotion is weakened when effective internal and external governance mechanisms are in place.